2017
DOI: 10.1108/rpj-12-2015-0188
|View full text |Cite
|
Sign up to set email alerts
|

Study of separation force in constrained surface projection stereolithography

Abstract: The fulltext of this document has been downloaded 112 times since 2017* Users who downloaded this article also downloaded: (2017),"A novel projection based electro-stereolithography (PES) process for production of 3D polymer-particle composite objects",

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 20 publications
0
49
0
2
Order By: Relevance
“…The average separation force is $18 N for each layer. Besides, there is no significant increase of separation force over the manufacturing process, which is often seen in conventional constrained surface SL processes [32,33]. The CAD model, fabricated picture, and the corresponding microscopic image are shown in Fig.…”
Section: Test Casementioning
confidence: 99%
“…The average separation force is $18 N for each layer. Besides, there is no significant increase of separation force over the manufacturing process, which is often seen in conventional constrained surface SL processes [32,33]. The CAD model, fabricated picture, and the corresponding microscopic image are shown in Fig.…”
Section: Test Casementioning
confidence: 99%
“…We showed that the suction force in FLOAT hydrogel printing is several hundred times less than that in continuous resin printing. This can potentially be explained by the fluid mechanics theory of Stefan's adhesion where separation force is inversely proportional to the cube of the separation distance and linearly proportional to the fluid viscosity (23,32). Although we did not measure the dead zone thickness in our continuous resin printing, it should be smaller than that in the CLIP method (120 µm).…”
Section: Discussionmentioning
confidence: 93%
“…It is also found that a porous substrate with PDMS coating is possible to address this challenge by providing direct contact of the air and PDMS and thus supplying the oxygen continuously. Preliminary study has proved the feasibility of using the porous transparent substrate coated with PDMS film as the constrained surface in SL [20]. Hence, this paper will further investigate how to design such porous PDMS-coated constrained surfaces, and how the various design parameters will affect the performance of the constrained surface in SL process.…”
Section: A Novel Polydimethylsiloxane Constrained Window With Air-difmentioning
confidence: 99%
“…The blue dotted curve is the recorded separation force during the printing process using the newly developed constrained surface, which is a PDMS film with design 3 air-diffusion-channel. The separation force model developed in our previous work [20] has also been used to calculate the theoretical peak separation forces using the two constrained surfaces. The red and blue dashed lines represent the calculated theoretical peak separation forces.…”
Section: Layer-by-layer Printing Of Objects With Wide Solid Cross Secmentioning
confidence: 99%
See 1 more Smart Citation